Implementing a robotics curriculum at an academic general surgery training program: our initial experience. Issue 3 (September 2016) - Winder, Joshua; Juza, Ryan; Sasaki, Jennifer; Rogers, Ann; Pauli, Eric; Haluck, Randy; Estes, Stephanie; Lyn-Sue, Jerome
Abstract The robotic surgical platform is being utilized by a growing number of hospitals across the country, including academic medical centers. Training programs are tasked with teaching their residents how to utilize this technology. To this end, we have developed and implemented a robotic surgical curriculum, and share our initial experience here. Our curriculum was implemented for all General Surgical residents for the academic year 2014–2015. The curriculum consisted of online training, readings, bedside training, console simulation, participating in ten cases as bedside first assistant, and operating at the console. 20 surgical residents were included. Residents were provided the curriculum and notified the department upon completion. Bedside assistance and operative console training were completed in the operating room through a mix of biliary, foregut, and colorectal cases. During the fiscal years of 2014 and 2015, there were 164 and 263 robot-assisted surgeries performed within the General Surgery Department, respectively. All 20 residents completed the online and bedside instruction portions of the curriculum. Of the 20 residents trained, 13/20 (65 %) sat at the Surgeon console during at least one case. Utilizing this curriculum, we have trained and incorporated residents into robot-assisted cases in an efficient manner. A successful curriculum must be based on didactic learning, reading, bedside training, simulation, and training in the operating room. Each program must examine their caseload and resident class to ensure proper exposure to this platform.